Tindakan Doxing Di Media Sosial Berdasarkan Undang-Undang Nomor 19 TAHUN 2016 Tentang Perubahan Atas Undang-Undang Nomor 11 Tahun 2008 Tentang Informasi Dan Transaksi Elektronik Dikaitkan Dengan Konsep Perlindungan Privasi - Dinda Salsabila; Sinta Dewi; Widati Wulandari (Qiyas : Jurnal Hukum Islam dan Peradilan, 2023)
Abstract: There is a phenomenon on the internet called doxing or the act of publishing private information about someone on the internet, typically with malicious intent. Doxing act violates people rights of their privacy of personal data. Not only with malicious intent, doxing act often carried out by victims of crime to seek justice. This study aims to determine the application of the protection of personal data principals from doxing act in ITE Law and to identify the legal liability of doxing actions on social media that is carried out by victims of crime in related to the concept of privacy protection.This research was conducted using normative juridical approach and descriptive analytical research specifications, namely by describing the issue with the phenomenon being studied as the research object, in this case doxing act, and then reviewed with secondary data. The data analysis was carried out using a qualitative juridical method.The results of the study show that in the ITE Law, the protection of personal data from doxing act can be found in Article 26 (1) regarding the consent to disclose personal data, Article 27 (1), (3), and (4) regarding to the content of personal data that is disclosed, and Article 30 (2) regarding to the method in obtaining the content or personal data that is disclosed. Doxing actions on social media carried out by victims of crime to seek justice in the concept of privacy protection can be held legally responsible under the ITE Law Article 26 by filing a lawsuit, criminal sanctions and fines based on Article 45 (1), (3), and (4) and Article 46 (2), or administrative sanctions based on the Ministry of Communication and Informatics Regulation No. 20 of 2016 Article 36 such as verbal and written warnings, temporary suspension of activities and/or announcements on online websites. Keywords: Privacy and Personal Data Protection, Doxing, Legal Liability